Penurunan Konsentrasi Anion Fosfat dan Sulfat dalam Air Limbah Hasil Proses Pengolahan Senotim dengan Metode Elektrokoagulasi - Kharistya Rozana; Devi Swasti Prabasiwi; Dewi Puspa Ariany (Eksergi, 2020)
Indonesia has rare earth mineral resources that have the potential to be processed into beneficial products for human life. In the processing of rare earth mineral resources rarely needed waste treatment devices to reduce contaminants in liquid waste process results. The method of processing with the electrocoagulator system is used because its does not require high levels of technology and costs. In research conducted wastewater treatment process results of xenotime by using method of electrocoagulation with variation of voltage and time of contact. Digestion of xenotime sand using concentrated sulfuric acid and in the content of xenotime sand there is a phosphate anion that binds with metal Y, Dy, Gd, La, Ce, Nd. Xenotime wastewater treatment process with electrocoagulation method is set at voltage variation 7V-13V with variation time of 0-120 minutes. The results of analysis with High Performance Liquid Chromatography (HPLC) showed that there is a decrease in the concentration of phosphate and sulfate anions in the filtrate of the processing results of xenotime wastewater using electrocoagulation method. The lowest concentrations of phosphate and sulfate anions occur in the 13 V voltage condition with 120 minutes of 1.180% and 0.564%.